Weaknesses and potentialities in the performance of mammograms by the Unified Health System in the city of Santa Maria / RS (Research, Society and Development, 2022)
The present study aimed to identify the weaknesses and potentialities experienced by women, to perform a mammography exam, made available by the Unified Health System. This is a study with a qualitative, exploratory and descriptive approach, carried out with users of public services in a city in the central region of Rio Grande do Sul, from August to October 2020. From the results obtained, three thematic categories emerged, namely: the importance of early detection, difficulties in accessing the mammography and strategies to expand the use of mammography. It was noticed through this study that, despite the availability of the exam on the public network, women do not always access it. Geographic, social and economic factors emerged as justifications for not attending the public health service to carry out the exam to aid the diagnosis. Fragile situations, such as the delay in acquiring the result, appear as a factor that discourages its realization.